Motricities of the South: Congada of St. Benedict in Ilhabela - Brazil - De Campos, Silmara Elena Alves; Corrêa, Denise Aparecida [UNESP]; Gonçalves Junior, Luiz (Federacion Espanola de Asociaciones de Docentes de Educacion Fisica (FEADEF), 2022)
Motricities of the South are social practices of games, fights, dances, parties, songs, stories and rituals with characteristics of a people / community located to the south, geographically or metaphorically, that involve tradition and resistance of such manifestations to colonialism and epistemological domination. The objective of this research is to understand the educational processes involved in the construction of the Motricities of the South of participants of the Congada de San Benedicto in Ilhabela, located on the north coast of the state of São Paulo, Brazil. With a phenomenological-inspired methodology, five people involved with the practice of the Congada were interviewed. The interviews were subjected to phenomenological analysis allowing the construction of the category: «Ancestrality, devotion and belonging to a party». It is possible to consider that the Motricities of the South, in the Congada de San Benedicto, involved the tradition and resistance of a people. These aspects are well maintained, they are raised, recreated, remembered, made present and projected among its participants in the daily process of living-life.
Motricidades del Sur: Congada de San Benedicto en Ilhabela - Brasil
Keywords: Congada; Educational Processes; Epistemologies of the South; Motricities of the South